2010
DOI: 10.3109/15622970903397722
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in antidepressant use-related seasonality change in suicide mortality in Hungary, 1998–2006

Abstract: The results suggest that decreasing seasonality of suicides could be a good marker of lowering rate of depression-related suicides in the population particularly among males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 39 publications
(68 reference statements)
5
26
0
1
Order By: Relevance
“…Internet search volume for the term “suicide” is lowest during the summer, the time where most studies report a peak in suicide deaths (Bjorksten et al, 2009; Reutfors et al, 2009; Sebestyen et al, 2009). The interpretation above explains this discrepancy between internet search activity and the seasonality of suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Internet search volume for the term “suicide” is lowest during the summer, the time where most studies report a peak in suicide deaths (Bjorksten et al, 2009; Reutfors et al, 2009; Sebestyen et al, 2009). The interpretation above explains this discrepancy between internet search activity and the seasonality of suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Though speculative, it may be that a sudden reduction in the duration of direct contact with a dependent represents a type of suicide risk in these women. Gender effect on seasonality of suicide was also noted in Hungary where a steadily increasing prescription rate for antidepressants was associated with a decrease in national suicide rate but significantly decreased seasonality of suicide only in males [70]. The suicide peak in spring has been considered to be a consequence of seasonal occurrence of depression-related suicides and the decreased seasonality of suicide in this Hungarian study was suggested to be a marker of lowering depression-related suicides (especially among men) as a result of increased antidepressant utilization in the population [70].…”
Section: Demographic Variablesmentioning
confidence: 98%
“…Winter months (from November till January) can be characterised by relatively more frequent negatively loaded tweets (November is especially outstanding). In the months of transition (February, September, October) negative tweets are relatively fewer (but their number 13 Some researchers investigating the relationship between suicides and antidepressants argue that taking medication could weaken or might even eliminate seasonality from suicide time series (Sebestyen et al, 2010). American data provide no support for this hypothesis, what is more, between 2012 and 2014 findings suggest even stronger seasonality effects.…”
mentioning
confidence: 99%